Peran Badan Usaha Milik Desa (BUMDes) dalam Meningkatkan Kesejahteraan Masyarakat di Desa Tanarawa Kecamatan Waiblama - Agsustinus Mundus; Makdalena Selviina Irwanti Kwuta; Maria Kapu Fao; Fransiskus X. Roga; Krsitofel Tonggenai (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze the role of Village-Owned Enterprises (BUMDes) in improving community welfare in Tanarawa Village, Waiblama District, Sikka Regency, and to evaluate the implementation of BUMDes programs. Tanarawa Village has primary economic potential in the plantation and food crop sectors, managed largely by the community as farmers. BUMDes was established as an instrument for village economic empowerment with the aim of increasing Village Original Income (PAD), strengthening the local economy, and maximizing the utilization of natural resources and human resources. This study used a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results indicate that BUMDes Tanarawa is still in the development stage, although it has been able to contribute to community welfare through the provision of basic necessities, training, outreach, and consultations related to business management. The success of BUMDes is influenced by government support, quality leadership, community participation, and transparent and accountable management. However, limited understanding by the community and village officials, as well as obstacles in implementing outreach, are inhibiting factors that need to be addressed. This study confirms that BUMDes plays a strategic role in local economic empowerment, improving community welfare, and equitable distribution of village economic growth.